Effect of Feed Restriction and Garlic Supplementation on Growth Performance, Nutrient Utilization and Meat Quality in Female Broiler’s Performance - Singh, Vishavdeep; Singh, Udeybir; Sethi, A. P.S. (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to study the effects of feed restriction and garlic supplementation on growth performance, nutrient utilization and meat quality in female broilers. In this study, 120, day-old female broilers were randomly distributed into 5 treatment groups each having 4 replicates with 6 birds in each replicate. Diets were formulated as per ICAR 2013 specifications and were fed in 3 phases. Treatment T1 served as control. The other treatments comprised: T2=T1 with feed restriction (10-12 h) at 8-17 days of age (DOA) with garlic supplementation, T3=T1 with feed restriction at 8-17 DOA (10-12 h) without garlic supplementation, T4=T1 with feed restriction at 18-27 DOA (10-12 h) with garlic supplementation, T5=T1 with feed restriction at 18-27 DOA (10-12 h) without garlic supplementation. Early feed restriction (8-17 DOA) without garlic supplementation reduced (P<0.05) the average body weight gain at 2nd and 3rd weeks of age. Garlic supplementation and late feed restriction (from 18-27 DOA) reduced (P<0.05) the average body weight gain at 4th week of age. Significantly (P<0.05) reduced average feed intake was observed in birds subjected to early feed restriction (8-17 DOA) with garlic (T2) and without garlic (T3) at 2nd and 3rd week of age as compared to control (T1). There was no significant effect on feed conversion ratio (FCR) of early and late feed restriction with or without garlic supplementation expect at 5th week of age where FCR was observed to be better (P<0.05) in T4 group of birds with late feed restriction and garlic supplementation as compared to control (T1) and late feed restriction without garlic supplementation (T5). Â Early and late feed restrictions with garlic supplementation (T2 and T4) resulted in significantly (P<0.05) higher crude protein and organic matter metabolizability as compared to control (T1. Garlic supplementation with early and late feed restriction (T2 and T4) improved meat quality, had significantly (P<0.05) better color and appearance, odour, texture, juiciness as well as overall acceptability than the control (T1). It was concluded that early feed restriction without garlic supplementation reduced the feed intake at 2nd and 3rd week of age and improved meat quality.